Autophagic flux restoration enhances the antitumor efficacy of tumor infiltrating lymphocytes. Issue 10 (28th October 2022) - Zhang, Chaoting; Sun, Yizhe; Li, Shance; Shen, Luyan; Teng, Xia; Xiao, Yefei; Wu, Nan; Lu, Zheming
Abstract : Background: Although adoptive cell therapy with tumor infiltrating lymphocytes (TILs) has mediated effective antitumor responses in several cancers, dysfunction and exhaustion of TILs significantly impair the therapeutic effect of TILs. Thus, it is essential to elucidate the exhausted characteristics of TILs and improve the antitumor effect of TILs by reversing their exhaustion. Here, we focused on the influence of autophagy on TILs in terms of T-cell activation, proliferation, and differentiation in vitro and in vivo. Methods: We first evaluated autophagy level of TILs and influence of spermidine treatment on autophagy levels of TILs. Furthermore, we assessed the proliferative potential, phenotypical characteristics, T cell receptor (TCR) repertoire and antitumor activity of TILs with and without spermidine treatment. Results: We found that autophagic flux of TILs, especially exhausted TILs that express inhibitory immunoreceptors and have impaired proliferative capacity and decreased production of cytotoxic effector molecules, was significantly impaired. The restoration of autophagic flux via spermidine treatment resulted in increased diversity of the TCR repertoire, reduced expression of inhibitory immunoreceptors (PD1, TIM3, or LAG3), enhanced proliferation and effector functions, which subsequently demonstrated the superior in vitro and in vivo antitumor activity of TILs. Our findings unveil that spermidine, as an autophagy inducer, reverses dysfunction and exhaustion of TILs and subsequently improves the antitumor activity of TILs. Conclusions: These data suggest that spermidine treatment presents an opportunity to improve adoptive TIL therapy for the treatment of solid tumors.